ChemInform Abstract: Copper‐Catalyzed Direct Transformation of Simple Alkynes to Alkenyl Nitriles via Aerobic Oxidative N‐Incorporation. Issue 9 (February 2016) - Huang, Xiaoqiang; Li, Xinyao; Jiao, Ning
Abstract: A novel direct transformation of aliphatic terminal alkynes to alkenyl nitriles through the incorporation of a nitrogen atom into the simple hydrocarbons is reported.